Optimalisasi Pelayanan Publik Melalui Penyusunan dan Penerapan Standar Pelayanan - Ella, Susy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
Bureaucratic reforms in the public service sector have been an important issue that demanded success, because this sector related to be community and has direct impact to them. However, public views on public services in Indonesia over the years are quite bad. Public service often describes as a sluggish, expensive and unfriendly. In order to fix that situation, government made some great effort to improve the quality of public services, such as through formulate and implementing service standards. Standards of service is expected to provide certain gurantees to the public in obtaining quality services that suit their needs. In others side, it can also lead to omproving government’s performance so the bureaucratic reforms in the public service sector can be achieved.